The Problem of Logico-Philosophical Origins of the Category of Modality - T. A. Selezneva (Vestnik MGIMO-Universiteta)
The article represents theoreticomethodological analysis of linguistic modality. It deals with the question of correspondence between the notions of modus and modality in philosophy and linguistics, as two related, but not identical categories. The author notices fundamental logico-philosophical conceptions of the modality and studies their impact on development of linguistic approaches to this category.